2003
DOI: 10.1049/el:20030928
|View full text |Cite
|
Sign up to set email alerts
|

Low-threshold CW GaInNAsSb/GaAs laser at 1.49 µm

Abstract: Low-threshold room temperature continuous wave 1.49 mm GaIn-NAsSb lasers are presented. Room temperature threshold current density of 1.1 kA=cm 2 was observed with a high external quantum efficiency of 40% and maximum output power of 30 mW from both facets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…While growth of GaInNAs QWs allows fabrication of near 1.3 mm VCSELs, manufacturers are hedging on going clear out to 1.3 mm or beyond because they have had yield problems which are similar to our observed growth sensitivity for these QW alloys and their reproducibility remains somewhat problematical. We have found that by incorporating Sb to form a quinary alloy, GaInNAsSb, the growth window for good 2-D epitaxy is not only expanded, but has enabled the incorporation of higher In and N compositions and realization of 1.5 mm low threshold current, high power edge emitting lasers [6][7][8] and the first monolithic 1.5 mm VCSELs grown on GaAs [8,9]. The major appeal of this quinary alloy is thus a SINGLE materials system for growth and processing which can produce not only the entire range of telecommunications devices, but enable significant integration of photonic and electronic devices with photonic crystal waveguides and resonators which could be the foundation technology for truly low cost, high speed, highly functional photonic integrated circuits that will provide high bandwidth networks to the desktop [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…While growth of GaInNAs QWs allows fabrication of near 1.3 mm VCSELs, manufacturers are hedging on going clear out to 1.3 mm or beyond because they have had yield problems which are similar to our observed growth sensitivity for these QW alloys and their reproducibility remains somewhat problematical. We have found that by incorporating Sb to form a quinary alloy, GaInNAsSb, the growth window for good 2-D epitaxy is not only expanded, but has enabled the incorporation of higher In and N compositions and realization of 1.5 mm low threshold current, high power edge emitting lasers [6][7][8] and the first monolithic 1.5 mm VCSELs grown on GaAs [8,9]. The major appeal of this quinary alloy is thus a SINGLE materials system for growth and processing which can produce not only the entire range of telecommunications devices, but enable significant integration of photonic and electronic devices with photonic crystal waveguides and resonators which could be the foundation technology for truly low cost, high speed, highly functional photonic integrated circuits that will provide high bandwidth networks to the desktop [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The active material InGaAsN is one of the strongest candidates for GaAs-based lasers emitting above 1.3 m. 3 Studies of wavelength extension using InGaAsN active regions have successfully realized lasers with wavelengths beyond 1.4 m. 4,5 Furthermore, the addition of antimony into InGaAsN during molecular beam epitaxy ͑MBE͒ growth 6,7 has been utilized to achieve GaInNAsSb quantum-well ͑QW͒ lasers emitting at 1.49 m, with a low threshold current density of 1.1 kA/ cm 2 . 7 However, these works have all employed MBE growth techniques.…”
Section: Introductionmentioning
confidence: 99%
“…7 However, these works have all employed MBE growth techniques. [4][5][6][7] The pursuit of InGaAsN QW lasers grown by MOCVD has led to high-performance diodes with record lowthreshold current densities of 200-210 A / cm 2 for emission wavelengths in the 1280-1320 nm range. 8 InGaAsN lasers grown by metalorganic vapor phase epitaxy ͑MOVPE͒ have been limited to = 1.38 m, where the threshold current density was 2.2 kA/ cm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…GaInNAs(Sb) edge-emitting lasers [1][2][3][4][5][6][7][8][9][10], vertical-cavity surface-emitting lasers (VCSEL) [11][12][13][14][15], and distributed feedback (DFB) lasers [16][17], grown monolithically on GaAs, have been demonstrated throughout the 1.2-1.6µm telecommunication bandwidth. They have several advantages over InP based devices: a larger conduction band offset which reduces temperature sensitivity and enhances differential gain, higher index contrast which decreases the necessary number of mirror pairs in distributed Bragg reflectors (DBRs) for VCSELs, native oxide apertures for current confinement, and lower cost wafers.…”
Section: Introductionmentioning
confidence: 99%